2016
DOI: 10.1093/rpd/ncw098
|View full text |Cite
|
Sign up to set email alerts
|

Shielding Effect of Lead Glasses on Radiologists’ Eye Lens Exposure in Interventional Procedures

Abstract: To study the shielding effect of radiologists' eye lens with lead glasses of different equivalent thicknesses and sizes in interventional radiology procedures. Using the human voxel phantom with a more accurate model of the eye and MCNPX software, eye lens doses of the radiologists who wearing different kinds of lead glasses were simulated, different beam projections were taken into consideration during the simulation. Measurements were also performed with the physical model to verify simulation results. Simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
1
16
1
1
Order By: Relevance
“…(130) Another study using Monte Carlo simulations and measurements and considering the effect of eye equivalence and the size of the glasses was performed by Hu et al (2017). According to the study, dose to the lens of the eye was reduced by a factor from 3 to 9 when wearing lead glasses with 20-cm 2 -sized lenses with an equivalent thickness ranging from 0.1-to 1.0-mm Pb.…”
Section: Assessment Of Dose To the Lens Of The Eye When Glasses Are Wornmentioning
confidence: 99%
“…(130) Another study using Monte Carlo simulations and measurements and considering the effect of eye equivalence and the size of the glasses was performed by Hu et al (2017). According to the study, dose to the lens of the eye was reduced by a factor from 3 to 9 when wearing lead glasses with 20-cm 2 -sized lenses with an equivalent thickness ranging from 0.1-to 1.0-mm Pb.…”
Section: Assessment Of Dose To the Lens Of The Eye When Glasses Are Wornmentioning
confidence: 99%
“…As shown in various Monte Carlo studies, 31,38 DRFs are highly dependent on the radiologist's distance from the tube, the angular position of the body, the tilt of the head, the height, the fit of the glasses to the face, and the tube position, which are roughly kept constant throughout an interventional procedure and can hardly be reproduced in a Monte Carlo or phantom-based analysis. On the other hand, DRFs do also depend on the glasses' lead equivalence and size although some studies indicate that there is no further improvement in the protection for lead equivalences higher than 0.35 mm Pb 31,39 and areas larger than 30 cm 2 per lens 39 . In this regard, the variations in the DRFs values do not seem to be attributable to different lead equivalences, as values higher than 0.35 mm Pb are frequently employed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding should be interpreted with caution, as few cases reported ever using lead glasses (n=167). Hu et al demonstrated a substantial reduction in radiation dose to the eye during FGIP with the use of lead glasses 24. The lack of trend in cataract risk with greater use of ceiling suspended shields and mobile floor shields is expected, as technologists typically stand outside the shielded area even when they are positioned near the patient.…”
Section: Discussionmentioning
confidence: 99%